Trends, Evolution and Future Research Directions in Waqf: A Bibliometric Analysis through Complex Networks - Aghilasse Kashi; Abdelkader Amor; Ali Al-Hashemi; Bechir Mahamat Issa (Journal of Islamic Monetary Economics and Finance, 2025)
This study employs a quali-quantitative approach that combines both bibliometric standard method and content analysis process to analyse WAQF publications and derive the current trends, evolution and future research directions in this important sector of Islamic finance industry. Our final dataset consists of 645 publications retrieved from the Scopus database and covers the period from 1975 to 2023. We use VOSviewer, Bibliometrix R-Package, and Microsoft Excel to conduct our three-stage analysis, namely bibliometric performance analysis, bibliometric network map analysis, and content analysis. Our descriptive analysis indicates that Malaysia and Indonesia top the list of most influential countries, hold the most relevant institutions, and accommodate on average half of the top ten most productive and impactful authors. Our network map analysis on the other hand ascertains the existence of four primary research themes namely, cash WAQF; WAQF as part of Islamic social finance ecosystem and its contribution to sustainable development; accountability; and governance and disclosure. An important policy implication of our results is that policymakers should integrate WAQF and Islamic social finance institutions into the mainstream financial system, establish effective regulatory and governance ecosystems for WAQF institutions to increase their ability to boost people’s social welfare, expand the spectrum of impact investment, and strengthen their contribution to more sustainable growth.